E silentio. Lettura di Guardando fotografie di Paul C. di Giovanni Giudici - Valese, Francesco (L'ospite ingrato, 2021)
Giovanni Giudici’s poem Guardando fotografie di Paul C. – collected in his last book of poems (Eresia della sera, 1999) – documents one of the author’s rare approaches to the figure and work of Paul Celan. Through a close reading of the text, which clarifies the inspirational occasion and the many references to the most essential expressions and themes of the poet’s last lyrical phase, the essay addresses the complex issue of Giudici’s relation with photography, to which other of his “poetic approaches” to poets of the past are linked, and investigates his reception of Celan’s poetry, by also examining the critical texts that Giudici wrote about the poet from Czernowitz and the possible mediation of other authors in this reading.